Phytochemistry of Tagetes minuta L. (Asteraceae) from Córdoba, Argentina: comparative study between essential oil and HS-SPME analyses - Vázquez, Ana María (2011)
A headspace solid-phase microextraction (HS-SPME) method followed by gas chromatography-mass spectrometry (GC-MS) and gas chromatography-flame ionization detection (GC-FID) is described for the analysis of volatile compounds in Tagetes minuta L. Five types of SPME commercial fibers including PA, PDMS, CAR-PDMS, PDMS-DVB and DVB-CAR-PDMS were investigated and the best extraction was achieved with the mixed fiber DVB-CAR-PDMS. Parameters for HS-SPME in terms of equilibrium time of HS, fiber exposition time and extraction temperature were also investigated. Additionally, the composition of inflorescences, leaves and stems was also studied separately by HS-SPME. As a result, 68 compounds were determined and 53 were identified. A comparison was made between results obtained by HS-SPME-GC-MS and steam distillation of essential oil of the aerial parts of the plant. In both analyses, the major components were: cis-tagetenone and trans-tagetenone. Using much smaller samples, a shorter extraction time and a simpler procedure, the HS-SPME method can achieve similar results to those obtained by EO analysis. In conclusion, the HS-SPME method is simple, rapid, effective and free of solvent, and can be used for the analysis of volatile compounds in samples of different populations of T. minuta.